Comparison of the effectiveness of a milk‐free soy‐maize‐sorghum‐based ready‐to‐use therapeutic food to standard ready‐to‐use therapeutic food with 25% milk in nutrition management of severely acutely malnourished Zambian children: an equivalence non‐blinded cluster randomised controlled trial. (18th June 2013) - Irena, Abel H.; Bahwere, Paluku; Owino, Victor O.; Diop, ElHadji I.; Bachmann, Max O.; Mbwili‐Muleya, Clara; Dibari, Filippo; Sadler, Kate; Collins, Steve
Abstract: Community‐based Management of Acute Malnutrition using ready‐to‐use therapeutic food (RUTF) has revolutionised the treatment of severe acute malnutrition (SAM). However, 25% milk content in standard peanut‐based RUTF (P‐RUTF) makes it too expensive. The effectiveness of milk‐free RUTF has not been reported hitherto. This non‐blinded, parallel group, cluster randomised, controlled, equivalence trial that compares the effectiveness of a milk‐free soy–maize–sorghum‐based RUTF (SMS‐RUTF) with P‐RUTF in treatment of children with SAM, closes the gap. A statistician randomly assigned health centres (HC) either to the SMS‐RUTF ( n  = 12; 824 enrolled) or P‐RUTF ( n  = 12; 1103 enrolled) arms. All SAM children admitted at the participating HCs were enrolled. All the outcomes were measured at individual level. Recovery rate was the primary outcome. The recovery rates for SMS‐RUTF and P‐RUTF were 53.3% and 60.8% for the intention‐to‐treat (ITT) analysis and 77.9% and 81.8% for per protocol (PP) analyses, respectively. The corresponding adjusted risk difference (ARD) and 95% confidence interval, were −7.6% (−14.9, 0.6%) and −3.5% (−9, 6., 2.7%) for ITT ( P  = 0.034) and PP analyses ( P  = 0.257), respectively. An unanticipated interaction (interaction P  < 0.001 for ITT analyses and 0.0683 for PP analyses) between the study arm and age group was observed. The ARDs were −10.0 (−17.7 to −2.3)% for ITT ( P  = 0.013) and −4.7 (−10.0 to 0.7) for PP ( P  = 0.083) analyses for the <24 months age group and 2.1 (−10.3, 14.6)% for ITT ( P  = 0.726) and −0.6 (−16.1, 14.5) for PP ( P  = 0.939) for the ≥24 months age group. In conclusion, the study did not confirm our hypothesis of equivalence between SMS‐RUTF and P‐RUTF in SAM management.